PERSPEKTIF PENDIDIKAN PEREMPUAN HJ. SITI RAIHANUN DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM - Lalu Muhammad Salikurrahman; Ali Rijwan; Indra Ryan Fauzi (Pusat Kajian dan Pengembangan Publikasi Ilmiah (PKPPI) Institut Agama Islam Hamzanwadi Nahdlatul Wathan Lombok Timur, 2024)
This research focuses on the views and efforts of Hj. Siti Raihanun Indonesian female figure, is related to women's education and its relationship to the values ​​of education in Islam. The research will explore the ideas of Hj. Siti Raihanun about the importance of education for women, into account the historical and socio-cultural context of that time. Hj. Siti Raihanun's efforts to expand women's access to education will be evaluated using the literature study method. The focus of the analysis is on Her ideas about women's education and its contribution to fighting for equal access to education, the principles of Islamic education which emphasize equality and the obligation to seek knowledge for all people, regardless of gender. Although the term ulama often refers to men, the role of women in education and civilization, especially as shown by Hj. Siti Raihanun, very important. This research explores the biography of Hj. Siti Raihanun underlined her dedication to Islamic education. It is hoped that the research results will provide a comprehensive picture of Hj. Siti Raihanun regarding women's education and its role in fighting for access to education for women in Lombok, its relevance to the values ​​of education in Islam.